Damage to the cervical spine with rheumatoid arthritis – difficulties of dianostics and patient management - E. I. Shmidt; A. A. Klimenko; A. V. Novikova; M. A. Nekrasov; L. P. Belikova; A. P. Raksha; V. V. Babenkov; G. A. Arutyunyan; M. R. Mazra (Научно-практическая ревматология)
The article presents a description of a 73-year-old patient with rheumatoid arthritis, complicated by the development of a neurological deficit in the form of tetraparesis. Magnetic resonance imaging of the cervical spine revealed destruction of the C2 odontoid process with its replacement by a pannus, atlantoaxial subluxation, compression of the proximal segments of the spinal cord, and a compression fracture of C5.